Educational administration : theory and practice - Aquino, Gaudencio V. (Manila, Philippines : Rex Book Store, 1999)
One of the school administrator's obligations specified in the Education Act of 1982 is that he or she "shall be accountable for the efficient and effective administration and management of the school." This particular provision is relevant in the context of the great challenges that our schools face today. Ours is a dynamic age characterized by scientific discovery, technological innovation, and rapid social and cultural change, and therefore our educational system - along with the schools, colleges, and universities both public and private encompassed by that system - must be in the forefront to meet those challenges.
Part I. Educational administration: an overview -- Part II. Foundations of educational administration -- Part III. The Practice of educational administration -- Part IV. Educational administration: today and tomorrow.
Includes bibliographical references and index.
Keywords: SCHOOL MANAGEMENT